Qualitative assessment of COVID-19 vaccination acceptance among healthcare workers in Pima County - Maiya Block Ngaybe; Harrison J. Schmitt; Stephanie Mallahan; Riley Sena; Samantha Werts; Brianna Rooney; Priscilla Magrath; Purnima Madhivanan (Taylor & Francis Group, 2023)
In the Spring of 2021, the COVID-19 vaccination was authorized for emergency use by the Food and Drug Administration. Healthcare workers (HCWs) are one of the most trusted sources of information for vaccination choices. However, HCWs at this time appeared to continue to have lower rates of COVID-19 vaccination uptake than expected in Arizona. The objective of this study was to examine factors that play a role in the vaccination decision-making process among Arizona HCWs. Between January and April 2021, 18 semi-structured interviews were conducted among physicians, emergency medical technicians and long-term care nurses in Pima County. The informed consent process was completed for each participant. The interview guide was informed by the Increasing Vaccination model to collect information on vaccination decision-making. A codebook was developed using an inductive approach. Coding and analysis was conducted using the software MAXQDA. Participants were primarily male (11/18, 61%) and white (11/18, 61%). Three participants identified as Hispanic. Initial themes that emerged included: mixed opinions concerning the innovations in COVID-19 vaccine development, access-related barriers, issues related to distribution inequities, concerns about misinformation and conspiracy theories, and dialogue concerning the benefits of requiring mandatory vaccination. The results gathered from this study indicate that there continues to be hesitancy among some healthcare professionals in Pima County. These results will be used to help Arizonan Health Departments promote rollout of novel vaccines more effectively through targeting relevant vaccination decision-making factors among HCWs.